Design, Control and Stabilization of a Transformable Wheeled Fire Fighting Robot with a Fire-Extinguishing, Ball-Shooting Turret - Tanyildizi, Alper Kadir (Mdpi, 2023)
In this study, a hybrid wheeled fire extinguisher robot has been created. The robot has a two-degrees-of-freedom (DoF) fire extinguisher gun turret. To control the disruptive effect of mechanical oscillations on the firing system during movement of the robot body, PID and SMC controllers are used. When closed on flat ground, the robot's five-piece transformable wheel construction allows it to travel swiftly. The wheel mechanism opens on tough terrain, allowing the wheel to assume a star-shaped configuration and enabling the robot to ascend by grasping onto obstructions. The three-dimensional mechanical design of the firefighter robot was designed first, followed by the kinematic model of the turret system and the three-dimensional Simscape model in the Matlab Simmechanic environment. Simulations of throwing fire-extinguishing balls at fire locations positioned at 20 m to 80 m horizontal and 1-30 m vertical distances were carried out on this model for three different scenarios (the robot is stationary, moving at constant speed and rotating around itself). The simulations resulted in a shooting success rate of 85.71% with PID and 95.23% with SMC (for a total of 105 shots). When the mistake rates were investigated, it was discovered that the constructed fire robot was usable in firefighting.
Keywords: firefighting robot; transformable wheeled robot; fire extinguisher ball; shooting system; shooting stabilization